(untitled) (LEARNing Landscapes, 2011)
The authors of this article have been writing together about practitioner research and inquiry for more than 25 years. In this article, they trace the roots of this interest to their work with K-12 teachers and school leaders over many years and their dissatisfaction with the idea that external researchers produce all the knowledge necessary to change teaching, learning and schooling. The article also highlights the notion of "inquiry as stance," which contrasts with the idea that inquiry is a project or a problem-solving technique.